F183. Oscillatory β activities in basal ganglia are associated with gait speed in PD. (May 2018) - Chen, Chiung Chu; Liu, Min-Yin; Tu, Po-Hsun; Yeh, Chien-Hung; Lu, Chin-Song
Abstract : Introduction: Gait disturbance in PD is complex and its pathogenesis remains unclear and the effect of medical and surgical is limited. Subthalamic nucleus (STN) DBS ameliorates main motor symptoms parkinsonism but the effect for gait disturbance is variable. Local field potential (LFP) recorded from such patients demonstrated synchronized activity at β frequency band (13–35 Hz). In addition, recent study suggested that LFP recorded from PPN at α range (4–10 Hz) correlated with gait speed in PD. Whether oscillations in STN is associated with gait disturbance in PD remains unknown. Here we investigate the relationship between STN LFP and gait performance of PD patients who underwent STN DBS surgery. Correlations were evaluated between STN LFP at different frequency range and gait speed in PD. Methods: 15 PD patients underwent bilateral STN DBS surgery for the treatments of advanced PD were recruited. Experiments took place 3–5 days after electrodes implantation. Patients were asked to rest comfortably with eye open (REST), then walk at their preferred speed (GAIT). LFPs were recorded from STN bilaterally, a triaxial accelerometry (ACC) was fixed over the spinous lumbar to record trunk acceleration. Relative gait speed (rGS) is estimated from ACC. Results: 1. Significant POSITIVE correlation was seen between peak frequency of LFP at REST and GAIT at β band but not α frequency band. 2. Significant POSITIVE correlation was seen between power of LFP at high β band (25–35 Hz) and gait speed. 3. Negative correlation was seen between power of LFP at low β band (15–25 Hz) and gait speed but didn't reach significance. Conclusion: 1. The gait speed of patients with PD is associated with STN LFP synchronized at high β band (25–35 Hz). 2. This study provided insight to how the basal ganglia modulate the gait performance in PD and shed light to the development of future adaptive DBS therapy for PD.